Work Dynamics and Employee Performance in Banking: Digital Escapism and Job Stress as Dual Mechanisms - Kartika, Ni Putu Silva Mona; Korry, Putu Dyah Permatha (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study examines the influence of work conflict, job training, transformational leadership, and organizational communication on employee performance, with digital escapism as a mediating variable and job stress as a moderating variable. Using a quantitative approach with data collected from 150 employees on Indonesian Banks. The analysis was performed using the SmartPLS method. The findings show that work conflict negatively affects employee performance, while job training, transformational leadership, and organizational communication have positive effects. Work conflict, leadership, and communication significantly influence digital escapism, though escapism itself does not affect performance or mediate any relationships. Job stress has a direct positive impact on performance but does not moderate the escapism, performance relationship. These results highlight the crucial role of organizational and leadership factors in improving employee performance within the context of digital transformation.